Coworker Networks and the Role of Occupations in Job Finding - Attila Gyetvai; Maria Zhu (Institute of Labor Economics (IZA), 2021)
Which former coworkers help displaced workers find jobs? We answer this question by studying occupational similarity in job finding networks. Using matched employer-employee data from Hungary, this paper relates the unemployment duration of displaced workers to the employment rate of their former coworker networks. We find that while coworkers from all occupations are helpful in job finding, there is significant heterogeneity in effects by occupation skill-level. For workers in low-skill jobs, coworkers who worked in the same narrow occupation as the displaced worker are the most useful network contacts. For workers in high-skill jobs, coworkers from different occupations are the most useful network contacts.
Keywords: J64; D85; J24; 330; networks; job search; former coworkers; unemployment duration; skill heterogeneity